Effects of native forest and human-modified land covers on the accumulation of toxic metals and metalloids in the tropical bee Tetragonisca angustula - Marcela de Matos Barbosa; Ana Carolina Coelho Fernandes; Rafael Souza Cruz Alves; Denise Araujo Alves; Fernando Barbosa Junior; Bruno Lemos Batista; Milton Cezar Ribeiro; Maria Fernanda Hornos Carneiro (Ecotoxicology and Environmental Safety, 2021)
The intensive shift on land cover by anthropogenic activities have led to changes in natural habitats and environmental contamination, which can ultimately impact and threat biodiversity and ecosystem services, such as pollination. The aim of this study was to evaluate the effect of native forest and human-modified land covers on the concentrations of chemical elements accumulated in the neotropical pollinator bee T. angustula. Eight landscapes, within an Ecological Corridor in the State of São Paulo, Brazil, with gradients of forest cover, spatial heterogeneity and varying land covers were used as sampling unities. Bees collected in traps or through actives searches had the concentration of 21 chemical elements determined by ICP-MS. Results show a beneficial effect of forested areas on the concentrations of some well-known toxic elements accumulated in bees, such as Hg, Cd, and Cr. Multivariate Redundancy Analysis (RDA) suggests road as the most important driver for the levels of Cr, Hg, Sb, Al, U, As, Pb and Pt and bare soil, pasture and urban areas as the landscape covers responsible for the concentrations of Zn, Cd, Mn, Mg, Ba and Sr in bees. The results reinforce the potential use of T. angustula bees as bioindicators of environmental quality and also show that these organisms are being directly affected by human land use, offering potential risks for the Neotropical ecosystem. Our study sheds light on how land covers (native forest and human-modified) can influence the levels of contaminants in insects within human-dominated landscapes. The generation of predictions of the levels of toxic metals and metalloids based on land use can both contribute to friendly farming planning as well as to support public policy development on the surrounding of protected areas and biodiversity conservation hotspots.